2017
DOI: 10.18632/oncotarget.15103
|View full text |Cite
|
Sign up to set email alerts
|

Protein calorie malnutrition, nutritional intervention and personalized cancer care

Abstract: Cancer patients often experience weight loss caused by protein calorie malnutrition (PCM) during the course of the disease or treatment. PCM is expressed as severe if the patient has two or more of the following characteristics: obvious significant muscle wasting, loss of subcutaneous fat; nutritional intake of <50% of recommended intake for 2 weeks or more; bedridden or otherwise significantly reduced functional capacity; weight loss of >2% in 1 week, 5% in 1 month, or 7.5% in 3 months. Cancer anorexiacachexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 194 publications
(222 reference statements)
1
51
0
10
Order By: Relevance
“…There have been numerous studies addressing nutritional deficit as a contributing factor of weight loss in patients with cancer. (75) There are no specific, defined, nutritional interventions for patients with advanced cancer undergoing chemotherapy treatment, and nutritional supplementation can increase fat mass but not muscle mass in patients with advanced cancer cachexia. (76) Although there is currently a clinical trial to address nutritional intervention in patients receiving chemotherapy treatment with whole-body protein synthesis as an outcome measure (https:// clinicaltrials.gov/ct2/show/NCT01871350), nutritional supplementation alone may not be adequate to prevent chemotherapy-induced cachexia-like symptoms.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…There have been numerous studies addressing nutritional deficit as a contributing factor of weight loss in patients with cancer. (75) There are no specific, defined, nutritional interventions for patients with advanced cancer undergoing chemotherapy treatment, and nutritional supplementation can increase fat mass but not muscle mass in patients with advanced cancer cachexia. (76) Although there is currently a clinical trial to address nutritional intervention in patients receiving chemotherapy treatment with whole-body protein synthesis as an outcome measure (https:// clinicaltrials.gov/ct2/show/NCT01871350), nutritional supplementation alone may not be adequate to prevent chemotherapy-induced cachexia-like symptoms.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…Thus, the association observed between low albumin and adverse outcomes could be driven by factors other than malnutrition. Furthermore, there is also a co‐existing systemic inflammatory process seen in cancer patients may be playing a role in the observed discordance in nutritional parameters and outcomes . It is reported that up to 50% of patients have an acute‐phase protein response, including increased albumin, at the time of upper‐gastrointestinal cancer diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients often suffer from protein-calorie malnutrition, which can lead to the loss of skeletal muscle and deterioration in the quality of life [6]. Proteins are important to develop and repair body tissues and are involved in the production of some hormones and enzymes.…”
Section: Proteinsmentioning
confidence: 99%